Effects of Bacterial Fertilizer on the Growth And Absorption of Cadmium and Lead in Maize - Shi, Xian; Meng, Lingheng; Wang , Tiantao; Tang, Yanhua (Bangladesh Journal of Botany, 2024)
This study involed a simulated pot experiment to examine the effect of different levels of bacterial fertilizer application on the growth of maize. As per the results stated, SJ-1 or 0.35 g/kg should be the Maximum and SJ-4 or 2.25 g/kg should be the Minimum but both data points are being referred to as Maxima. As per the results CK and SJ-1 showed no difference and SJ-3 had the lowest but both SJ-1 and SJ-3 are stated to be the lowest. The bioconcentration factor (Pb) and transfer factor (Cd and Pb) in maize were reduced the most following the 2.25 g/kg treatment. The application of the bacterial fertilizer was found to reduce the pH and the amounts of EDTA-Cd and EDTA in the soil. The amount of the bacterial fertilizer applied was found to be positively correlated with the Cd and Pb contents in the underground parts. The results suggested that the correct application of the bacterial fertilizer could promote the growth of maize. Bangladesh J. Bot. 53(2): 297-304, 2024 (June)